Puerpério e pandemia da Covid-19: a influência na rotina de mulheres brasileiras - Corradini, Ana Luisa (Universidade Federal de São Carlos, 2023)
Introduction: In March 2020, when the COVID-19 pandemic status was declared in Brazil, it was recommended that the population take measures to avoid contagion by viruses, such as social isolation and the use of masks. In April of the same year, pregnant women and puerperal women within 14 days of puerperium were considered a risk group for the disease, considering that these women are more susceptible to contracting viral infections. Goal: Check the impact of the pandemic on the routine of Brazilian postpartum women from the profile description of Brazilian postpartum women during the COVID-19 Pandemic, their prophylaxis habits, isolation and breastfeeding and identification of factors associated with the effects of this period on breast-feeding. Methodology: This is a descriptive observational study, approved by the Ethics Committee in Research with Human Beings of the Federal University of São Carlos (CAAE: 31253520.3.0000.5504). The study was carried out based on a questionnaire about socioeconomic characteristics, obstetric history, prophylaxis data and breastfeeding data maternal, filled out via Google Forms. Were invited to participate, Brazilian women in puerperal period that they gave birth from the pandemic decree in Brazil (March 2020), until the last month of application of the questionnaire (March 2021). Results: 312 were received valid answers, from postpartum women from all over Brazil. According to the results of this study, there was a prevalence of women of higher social class, with higher family income and schooling. As for social isolation, it was identified that most women performed partial isolation, as they go out for domestic activities. Finally, among the variables, it was observed that age, education, race/color and postpartum period were the most were influenced by the pandemic in relation to breastfeeding. Among women aged 19 to 29, with lower schooling, black and indigenous women and/or with a longer postpartum period, there was a greater positive influence. Conclusion: The pandemic exerted an important influence on the daily lives of postpartum women, in addition to contributing to greater adherence and frequency of breastfeeding in some women. Finally, the importance of new studies that investigate these factors and their influence.
Postpartum and Covid-19: the influence in routine of brazilian women
Keywords: Saúde da mulher; Período Pós-Parto; Aleitamento Materno; Pandemia por COVID-19; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL